Mini Review: Anticholinergic Activity as a Behavioral Pathology of Lewy Body Disease and Proposal of the Concept of "Anticholinergic Spectrum Disorders". (22nd September 2016) - Hori, Koji; Konishi, Kimiko; Hosoi, Misa; Tomioka, Hiroi; Tani, Masayuki; Kitajima, Yuka; Hachisu, Mitsugu
Abstract : Given the relationship between anticholinergic activity (AA) and Alzheimer's disease (AD), we rereview our hypothesis of the endogenous appearance of AA in AD. Briefly, because acetylcholine (ACh) regulates not only cognitive function but also the inflammatory system, when ACh downregulation reaches a critical level, inflammation increases, triggering the appearance of cytokines with AA. Moreover, based on a case report of a patient with mild AD and slightly deteriorated ACh, we also speculate that AA can appear endogenously in Lewy body disease due to the dual action of the downregulation of ACh and hyperactivity of the hypothalamic-pituitary-adrenal axis. Based on these hypotheses, we consider AA to be a behavioral pathology of Lewy body disease. We also propose the concept of "anticholinergic spectrum disorders, " which encompass a variety of conditions, including AD, Lewy body disease, and delirium. Finally, we suggest the prescription of cholinesterase inhibitors to patients in this spectrum of disorders to abolish AA by upregulating ACh.